2005
DOI: 10.1016/j.envpol.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of arsenate on soils. Part 1: Laboratory batch experiments using 16 Chinese soils with different physiochemical properties

Abstract: The Langmuir two-surface equation fits arsenate adsorption onto soils. AbstractLaboratory batch experiments were carried out to study the adsorption of arsenate on 16 Chinese soils with different physicochemical properties. Wide differences in arsenate adsorption were observed, and the Jiangxi and Hubei soils were more effective sorbents for arsenate than other soils. The Langmuir one-surface and two-surface equations were used to model the arsenate adsorption data. Except for the Jiangxi and Hubei soils, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 20 publications
0
28
1
Order By: Relevance
“…Langmuir one-site and Langmuir two-site equations [20] were used to describe the adsorption of arsenate, As/F, and As/P on the Fe-Ce adsorbent. The Langmuir one-site equation is:…”
Section: Adsorption Equationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Langmuir one-site and Langmuir two-site equations [20] were used to describe the adsorption of arsenate, As/F, and As/P on the Fe-Ce adsorbent. The Langmuir one-site equation is:…”
Section: Adsorption Equationsmentioning
confidence: 99%
“…The Langmuir one-site and two-site equations [16,20,23] were used to fit the adsorption isotherms of arsenate at a given concentration range ( Figure S1, Supplementary material). As shown in Table 1, the predicted adsorption capacities (Q 0 and Q) were 1.33 mmol g −1 and 1.85 mmol g −1 for the Langmuir one-site and two-site equations, respectively.…”
Section: Adsorption Equilibrium Isotherm Of Arsenatementioning
confidence: 99%
See 2 more Smart Citations
“…The effects of common environmental conditions on the adsorption of arsenicals onto TiO 2 surface have been studied a lot (Jiang et al, 2005;Xu et al, 2008) but studies on the influence of soil properties on the generation of ROS by TiO 2 are very rare. Ng et al (2013) once reported the production of OH by TiO 2 was influenced by its stability in solution, and the stability of TiO 2 in soil slurries appeared to be correlated with soil properties (Fang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%